The Potential of Aloe Vera Application as Coagulant in Reduce PAC Consumption in Drinking Water Treatment Process - Yaniza Dela Daza; Temmy Wikaningrum (Jurnal Serambi Engineering, 2024)
This study investigates the use of aloe vera as an alternative coagulant to PAC in the treatment of the Tarum Barat Canal, which is vital to local communities but faces declining water quality due to upstream land use changes and human activities. The aim is to assess the potential of aloe vera to reduce the consumption of PAC in drinking water treatment and to determine the optimal dosage for effective turbidity reduction and pH regulation. Primary data were collected through laboratory experiments evaluating key water indicators, while secondary data from PT. X provided additional insight into the canal's water quality from January to July 2023. The results show that PAC alone achieves a turbidity removal efficiency of 96.76%, while the combination of Aloe Vera and PAC achieves 95.03%. Both treatments maintain pH levels within the safe range set by the Indonesian Ministry of Health. The optimum dosage was found to be 17 ppm PAC with 180 ppm Aloe Vera, which meets drinking water standards and reduces PAC use by 56.25%